A phase I study evaluating the effect of everolimus on the pharmacokinetics of midazolam in healthy subjects - Urva, Shweta; Bouillaud, Emmanuel; Delaney, Rosemary; Jappe, Annette; Cheung, Wing (Journal of clinical pharmacology, 2013)
The selective mammalian target of rapamycin (mTOR) inhibitor everolimus has demonstrated competitive inhibition of cytochrome P450 enzyme (CYP) 3A4 in vitro; however, its influence on CYP3A4 activity in humans is unknown. This study examined the influence of everolimus on the pharmacokinetics of midazolam, a sensitive CYP3A4/5 substrate, and its 1-hydroxy metabolite in 25 healthy male subjects. Compared with administration of oral midazolam 4 mg/day alone, coadministration with everolimus 10 mg/day increased the midazolam maximum plasma concentration (C(max)) by 25% and the area under the plasma concentration-time curve (AUC) by 30%. The C(max) and AUC of 1-hydroxymidazolam increased by 20% and 25%, respectively. Concomitant administration of everolimus with midazolam did not change the midazolam metabolic ratio (i.e., the ratio of 1-hydroxymidazolam AUC to midazolam AUC) or the midazolam or 1-hydroxymidazolam terminal half-lives (geometric mean ratios for midazolam + everolimus vs. midazolam alone of 0.96, 1.03, and 1.06, respectively). These results suggest everolimus may affect the bioavailability, but not the systemic clearance, of orally coadministered CYP3A4 substrate drugs.